The Interpretation of Dyspnea in the Patient with Asthma - Marc H. Lavietes (Pulmonary Medicine)
Physicians have noted dyspnea in severely ill asthmatic patients to be associated with fright or panic; in more stable patients dyspnea may reflect characteristics including lung function, personality and behavioral traits. This study evaluates the symptom of dyspnea in 32 asthmatic patients twice: first when acutely ill and again after an initial response to therapy. Spirometry was performed, dyspnea quantified (Borg scale), and panic assessed with a specialized measure of acute panic (the acute panic inventory (API)) in the 32 patients before and again after treatment. After treatment, questionnaires to evaluate somatization and panic disorder were also administered. When acutely ill, both the API and all spirometric measures (PEFR; FEV1; IC) correlated with dyspnea. Multiple linear regression showed that measures of the API, the peak expiratory flow rate, and female sex taken together accounted for 41% of dyspnea in acute asthma. After treatment, the API again predicted dyspnea while spirometric data did not. Those subjects who described themselves as having chronic panic disorder reported high grades of dyspnea after treatment also. We conclude that interpretations of the self-report of asthma differ between acutely ill and stable asthmatic patients.